ANALISIS PENGELOLAAN KEUANGAN UMKM DESA KOTA PARI DALAM PENINGKATAN EKONOMI PASCA PANDEMI COVID-19 - Syaula, Maya; Amelia, Ocdy; Purnomo, Cahyo (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This study aims to determine the management implemented by Micro, Small and Medium Enterprises or UMKM in Kota Pari Village. Good financial management can help UMKM in advancing their business. Through good management, it is hoped that the UMKM community in Kota Pari village will be more active in improving financial management. This type of research is a case study with data analysis techniques, namely quantitative descriptive analysis. The results of this study are that UMKM actors in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency as a whole do not understand and implement financial management properly and correctly in accordance with science. This happens because of a lack of understanding of business actors and a lack of guidance, training and outreach regarding how to manage MSME finances properly. From the results of the analysis, UMKM actors in Kota Pari Village feel that their business can only run locally, meaning in that village. However, if a deeper analysis is carried out, the UMKM in the Kota Pari village have excellent economic growth potential, especially after the Covid-19 pandemic. However, this must be supported by the authorities.